Shrimp allergy leading to severe transfusion reaction: A case report - Myrthe E. Sonneveld; Sophie J. Bernelot Moens; Jolanda van denAkker; Josephine M. I. Vos; Arjan J. Kwakernaak (eJHaem)
Abstract Background Transfusion reactions occur at an estimated incidence of 2 per 1.000 transfused products. Anaphylactic transfusion reactions are rarer, and seen in 1 per 10.000 transfusions, and are mostly related to platelet transfusions. Here, we describe a rare cause of a transfusion reaction. Case presentation A 19‐year‐old man underwent an allogeneic haematopoietic stem cell transplantation for sickle cell disease and developed an anaphylactic shock following a platelet transfusion, after excluding all common causes. The patient reported a shrimp allergy, and one of the blood/platelet donors had consumed shrimp the day before donation. Elevated levels of specific immunoglobulin E (IgE) directed against shrimp and tropomyosin allergens were found in the patient. Subsequent transfusions were performed with apheresis platelets from selected donors who were instructed to avoid shrimp consumption, and these transfusions were uneventfully. Conclusion When a severe transfusion reaction occurs in a patient with a known food allergy, an IgE‐mediated (food‐related) transfusion reaction should be considered after excluding other causes.